Effect of cane trash management on soil-moisture conservation, soil fertility and yield of sugarcane (Saccharum officinarum) - SWAMY, K RAMALINGA; JAMUNA, P; RAO, T K V V MALLIKARJUNA; RAJU, A PADMA (The Indian Journal of Agricultural Sciences, 2013)
A study was taken up on cane trash management through use of compost culture, urea, single superphosphate in relation to soil moisture conservation during ealy part of crop growth, recycling of nutrients and soil fertility improvement in the later part of the sugarcane cultivation. Trash mulching at 3 tonnes/ha and use of composting microbial culture, urea land single superphosphate conserved soil mositure under sugarcane (Saccharam officinarum L.) cultivation. Cane traSh management helped in conserving soil,moisture in the initial stages of crop growth, which decomposed subsequently by the action of compost culture, urea and superphosphate leading to improvement in soil nitrogen and phosphorus. However, the potassium removal by the crop was higher than the added potassium, thereby leading to depletion of soil reserves. Trash mulching at 3 tonnes/ha and urea application at 10 kg/ha gave highest cane and sugar yields.